2014
DOI: 10.1021/mz500260h
|View full text |Cite|
|
Sign up to set email alerts
|

Origin of Stress Overshoot during Startup Shear of Entangled Polymer Melts

Abstract: Using Brownian dynamics simulation, we determine the chain orientation and stretching and their connection to stress overshoot in an entangled polymer melt undergoing startup shear at rates lower than the reciprocal of the Rouse time yet higher than the reciprocal of the reptation time. In this rate regime, the prevailing tube theory attributes the stress overshoot to alignment of the primitive chain. In contrast, our results reveal that there is substantial chain stretching that persists well beyond the Rouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
78
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(94 citation statements)
references
References 34 publications
(48 reference statements)
11
78
5
Order By: Relevance
“…We have revisited the stress-optical rule of flexible polymers to examine if the shear component of the orientational anisotropy of the subchain, S xy (t ), can grow monotonically with t when the squared stretch ratio l (t ) 2 exhibits the overshoot as claimed by Lu et al 3,4) Expanding l(t ) 2 and the segmental shear orientational anisotropy O xy (t ) with respect to the shear rate g 4 , we found that the overshoot of S xy (t ) is a nonlinearity of the order of g 4 3 and emerges at lower g 4 compared to the overshoot of l(t ) 2 (that is a nonlinearity of the order of g 4 4 ), as long as SOR is valid. In other words, l(t ) 2 can monotonically grow even when S xy (t ) exhibits the overshoot, but the overshoot of l(t ) 2 is always accompanied by the overshoot of S xy (t ).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…We have revisited the stress-optical rule of flexible polymers to examine if the shear component of the orientational anisotropy of the subchain, S xy (t ), can grow monotonically with t when the squared stretch ratio l (t ) 2 exhibits the overshoot as claimed by Lu et al 3,4) Expanding l(t ) 2 and the segmental shear orientational anisotropy O xy (t ) with respect to the shear rate g 4 , we found that the overshoot of S xy (t ) is a nonlinearity of the order of g 4 3 and emerges at lower g 4 compared to the overshoot of l(t ) 2 (that is a nonlinearity of the order of g 4 4 ), as long as SOR is valid. In other words, l(t ) 2 can monotonically grow even when S xy (t ) exhibits the overshoot, but the overshoot of l(t ) 2 is always accompanied by the overshoot of S xy (t ).…”
Section: Resultsmentioning
confidence: 96%
“…Fig.2c. Thus, the claim by Lu et al 3,4) 3,4) as long as SOR is valid at those g 4 in the moderately nonlinear regime.…”
Section: Orientational Anisotropy and Stretch Of Subchain In The Linementioning
confidence: 84%
See 3 more Smart Citations